psol09 - Solutions to Homework 9, Math 55 Section 6.4 2....

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Solutions to Homework 9, Math 55 Section 6.4 2. The generating function is 1 + 4 x + 16 x 2 + 64 x 3 + 256 x 4 = 4 n =0 (4 x ) n = 1- (4 x ) 5 1- 4 x = 1- 1024 x 5 1- 4 x . 8. (a) Since ( x 2 + 1) 3 = (1 + x 2 ) 3 = 3 i =0 ( 3 i ) x 2 i , we have a n = ( 3 n/ 2 ) if 0 n 6 and n is even; otherwise, a n = 0. (b) Similarly, (3 x- 1) 3 = 3 n =0 ( 3 n ) (3 x ) n (- 1) 3- n ; thus, if 0 n 3, then a n = (- 1) 3- n 3 n ( 3 n ) , and otherwise a n = 0. (c) We have 1 1- 2 x 2 = k =0 (2 x 2 ) k = k =0 2 k x 2 k . Thus, if n is even, then a n = 2 n/ 2 , while if n is odd, then a n = 0. (d) The given function is equal to x 2 (1- x )- 3 . By the binomial theorem, this is equal to x 2 k =0 (- 3 k ) (- 1) k x k = k =0 (- 3 k ) (- 1) k x k +2 . Thus, to get a term x n we set k = n- 2; if n < 2, this gives a n = 0, while if n 2, this gives a n = (- 3 n- 2 ) (- 1) n . By the result of example 8 on page 438, we can write this as a n = ( n n- 2 ) = ( n 2 ) . (e) The given function is equal to x- 1 + n =0 3 n x n . Thus, a = 3- 1 = 0; a 1 = 3 1 + 1 = 4; and if n 2, then a n = 3 n . (f) We rewrite 1+ x 3 (1+ x ) 3 = 1- 3 x +3 x 2 (1+ x ) 3 = 1- 3 x (1+ x ) 2 . This is equal to 1- 3 x k =0 (- 2 k ) x k = 1- k =0 3 (- 2 k ) x k +1 . Thus, we have a = 1, while for n 1, we set k = n- 1 to get the x n term, so a n =- 3 (- 2 n- 1 ) . Again using example 8, we can rewrite this as a n = 3 n (- 1) n . (g) If we multiply the top and bottom by 1- x , then this is equal to x- x 2 1- x 3 = ( x- x 2 ) k =0 x 3 k = k =0 ( x 3 k +1- x 3 k +2 ). Thus, we get a n = , if n (mod 3); 1 , if n 1 (mod 3);- 1 , if n 2 (mod 3) . Alternately, let =- 1+ i 3 2 ; then we can factor 1 + x + x 2 = (1- x )(1- x ), where =- 1- i 3 2 is the complex conjugate. We can now use partial fractions to write x 1 + x + x 2 = 1 i 3 1 1- x- 1 1- x = 1 i 3 X n =0 ( n- n ) x n . Thus, a n = 1 i 3 ( n- n ). Since = e 2 i/ 3 and = e- 2 i/ 3 , this can be rewritten in terms of real numbers as a n = 2 3 sin( 2 n 3 ). (h) The given function expands to- 1 + k =0 (3 x 2 ) k /k ! =- 1 + k =0 (3 k /k !) x 2 k . Thus, if n is odd, then a n = 0; a =- 1 + 1 = 0; and if n 2 is even, then a n = 3 n/ 2 / ( n/ 2)!....
View Full Document

Page1 / 4

psol09 - Solutions to Homework 9, Math 55 Section 6.4 2....

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online